STRATEGI PEMERINTAH DALAM MEMPERKECIL ANGKA PENGANGGURAN DI KECAMATAN TAMPAN KOTA PEKANBARU - ROMIKA "; ERNAWATI " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Government Strategy In Unemployment Decreasesin District Handsome Pekanbaru. This study aimstoreducethe unemployment rateinthe cityof Pekanbaru, especially in District Handsome. This studyis descriptive equalitative wheredata collection is donebysnowball sampling technique. The results ofthis study indicatethatit is not the maximum execution Unemployment Decreasesin District Handsome Pekanbaru. Minimizeun employment in the District Handsome Pekanbaruhas not gone wellin implementingefforts toreduceun employment. Indicatorof the weaknessandthe threat ofjob seekersmostjob seekersfresh outof schoolanddo nothave the skills and expertise. Then the job seekersdo not want to fill jobsoutside the area. Andalsojob seekers who come from outside the areais alsobecomingone of the problemsthat hinderthe governmentin reducing unemployment ratein the Distric tHandsome Pekanbaru.Keywords:Strategy, Unemployment, Strengths, Weaknesses, Opportunities, Threats